Rezidenční dům v Brně - Pisárkách, technologická etapa zastřešení - Bárta, Patrik (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Bakalářská práce se zabývá stavebně technologickým řešením zastřešení rezidenčního domu v Brně, Pisárkách. Řeší realizaci dvouplášťové střechy pultové a sedlové. Práce obsahuje technickou zprávu, rozpočet a časový plán, technologický předpis, kontrolní a zkušební plán a další technickou dokumentaci dle zadání.

The bachelor thesis deals with the constructive and technological solution of roofing residential building in Brno, Pisárky. It solves implementation of double-shell shed roof and saddle roof. The work includes technical report, budget and time frame, technological regulation, inspecting and test plan and other technical documentation in compliance with assignment.
Residential Building in Brno - Pisárky, Constructive and Technological Solutions of Roofing
Keywords: Zastřešení; pultová střecha; sedlová střecha; technická zpráva; rozpočet a časový plán; kontrolní a zkušební plán; bezpečnost práce; hydroizolace.; Roofing; shed roof; saddle roof; technical report; budget and time frame; inspecting and test plan; occupational safety; waterproofing.